2020
DOI: 10.1590/2175-8239-jbn-2019-0205
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy assessment in chronic kidney disease: validation of the PAIR instrument for use in Brazil

Abstract: Individuals with chronic kidney disease (CKD) use polypharmacy, which, in combination with renal impairment, exposes them to the risk of drug-related problems (DRPs). There are no available tools in Brazil to systematically assess the pharmacotherapy and management of DRPs in this population. Therefore, the objective of this work was to validate the PAIR instrument (Pharmacotherapy Assessment in Chronic Renal Disease) for use in Brazilian Portuguese. This is a retrospective longitudinal observational study. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
1
8
0
3
Order By: Relevance
“…However, it has been confirmed by research that polypharmacy was combined with renal impairment and exposed patients to the risk of drug-related problems. 42 The concurrent use of multiple medications increased the risk of kidney dysfunction among older adults because it could burden the ageing kidneys to excrete multiple pharmaceutical ingredients and their metabolites. 43 The results of other relevant studies on the impact of polypharmacy on kidney function also indicated that every additional drug prescribed among older adults will have an independent and immediate harmful impact on their kidney function.…”
Section: Open Accessmentioning
confidence: 99%
“…However, it has been confirmed by research that polypharmacy was combined with renal impairment and exposed patients to the risk of drug-related problems. 42 The concurrent use of multiple medications increased the risk of kidney dysfunction among older adults because it could burden the ageing kidneys to excrete multiple pharmaceutical ingredients and their metabolites. 43 The results of other relevant studies on the impact of polypharmacy on kidney function also indicated that every additional drug prescribed among older adults will have an independent and immediate harmful impact on their kidney function.…”
Section: Open Accessmentioning
confidence: 99%
“…O grupo de pacientes mais propícios para o surgimento desta situação são os idosos, onde apresentam riscos mais elevados de serem vítimas de interações medicamentosas, em função de alterações fisiológicas importantes, que ocorrem com o envelhecimento, principalmente nas funções hepática, renal e cardíaca, além da diminuição da massa muscular, do nível de albumina sérica e da quantidade total de água no organismo (MARQUITO et al, 2020).…”
Section: Interações Medicamentosasunclassified
“…A idade por si só não representa um fator de risco, mas um indicador para comorbidade, pois neste grupo a farmacocinética alterada e o advento da polifarmácia são as variáveis mais diretamente associadas às RAM. Idade avançada, sexo feminino, número elevado de fármacos, maiores doses e tratamentos prolongados, reações adversas prévias, enfermidades subjacentes, valoração clínica inadequada, mau cumprimento terapêutico (apego terapêutico), automedicação, estado nutricional alterado, alterações em farmacocinética e, farmacodinâmica são grandes fatores predisponentes para o surgimento das reações adversa a medicamentos um terço deste episódio são dependentes das doses (MARQUITO et al, 2020).…”
Section: Reações Adversas a Medicamentosunclassified
See 1 more Smart Citation
“…The article “ Pharmacotherapy assessment in chronic kidney disease: validation of the pair instrument for use in Brazil ” 1 , authored by Alessandra Batista Marquito, Hélady Sanders Pinheiro, Natália Maria da Silva Fernandes, and Rogério Baumgratz de Paula, aimed to validate the PAIR (Pharmacotherapy Assessment in Chronic Renal Disease) instrument for use in Brazilian Portuguese. Jean-François Desrochers and collaborators, from the University of Montreal, Canada 2 , originally developed this instrument.…”
mentioning
confidence: 99%